Information Digitalization, Budget Participation, And Apparatus Competence On Village Fund Accountability - Elvira Zeyn; Glen Lazwardi Qurba; Ridwan Ridwan; Haris Resmawan (CV Edujavare Publishing, 2026)
Village fund management in Indonesia faces persistent challenges related to transparency and accountability, with corruption in the village fund sector amounting to IDR 233 billion across 154 cases in 2021 alone. This study aims to examine the influence of information digitalization, budget participation, and village apparatus competence on the accountability of village fund management in Padalarang District, West Bandung Regency. A quantitative approach was employed, using primary data collected through structured questionnaires distributed to 81 village officials and community members involved in village fund management across ten villages. Multiple linear regression analysis was conducted using SPSS. The results indicate that information digitalization, budget participation, and village apparatus competence each exert a positive and significant effect on accountability, both individually and simultaneously. Budget participation contributes the largest partial effect at 31.7%, followed by information digitalization at 21.7%, and village apparatus competence at 13.9%. Collectively, the three variables explain 67.3% of the variance in accountability. These findings lend empirical support to the Technology Acceptance Model, Participatory Budgeting Theory, and Human Capital Theory in the context of village-level governance. The study contributes a multi-factor empirical framework to the literature on village fund accountability and recommends that village governments prioritize genuine community participation throughout the budget cycle, strengthen digital infrastructure, and enhance apparatus competence through regular training and equitable compensation